Preparation method of photocatalytic deodorizing filter screen
By loading TiO2 quantum dots on porous WO3 nanofibers in a photocatalytic odor removal filter and fixing TiO2@WO3 nanocomposite fibers with conductive epoxy resin coating, the shortcomings of existing photocatalytic materials in photogenerated carrier separation and photoquantum efficiency are solved, and efficient photocatalytic odor removal effect and corrosion resistance are achieved.
Patent Information
- Application Number
- CN202411956566.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-29
- Publication Date
- 2025-04-25
AI Technical Summary
The existing photocatalytic materials still need to be improved in terms of photogenerated carrier separation and photoquantum efficiency, and the coating effect of polymer film forming substances on photocatalytic nanoparticles will cause a reduction in photocatalytic activity. Metal filters will rust during long-term use, resulting in peeling off the surface photocatalytic coating and reducing service life.
By loading TiO2 quantum dots on porous WO3 nanofibers, a TiO2@WO3 nanoheterojunction is constructed, and TiO2@WO3 nanocomposite fibers are fixed on the surface of the metal filter screen using a conductive epoxy resin coating to improve photocatalytic activity and corrosion resistance.
It achieves efficient photocatalytic odor removal effect, improves the visible photocatalytic activity and corrosion resistance of photocatalytic materials, and extends the service life of the filter.
Smart Images

Figure BDA0005216020080000051 
Figure BDA0005216020080000061 
Figure BDA0005216020080000071
Abstract
Description
Technical Field
[0001] The invention relates to the preparation of environmental purification materials, and in particular to a method for preparing a photocatalytic deodorizing filter. Background Art
[0002] At present, with the continuous expansion of the scale of cities in my country, the amount of urban domestic waste generated is increasing year by year. Due to the fact that domestic waste, especially organic compounds containing nitrogen and sulfur (such as proteins, amino acids, etc.) in kitchen waste are easy to rot and ferment, malodorous gases such as ammonia and hydrogen sulfide will be produced, which seriously threatens the personal safety of cleaning staff and surrounding residents. It has become an important environmental protection issue that needs to be solved urgently and is related to people's livelihood. In response to this air pollution problem, the negative pressure system is currently mainly used to collect odor into purification equipment, and the removal of garbage odor is achieved through the coordinated use of multiple purification technologies such as adsorption, low-temperature plasma oxidation, and photocatalysis. Among them, photocatalytic technology has attracted widespread attention due to its outstanding advantages in strong oxidation and decomposition ability.
[0003] In garbage odor purification equipment, photocatalytic technology mainly involves fixing the photocatalytic material load on the filter surface for photocatalytic reaction. From the perspective of actual application, there are still many problems to be solved: First, the current photocatalytic materials still need to be further improved in terms of photogenerated carrier separation and photoquantum efficiency. Second, the application of existing nano-photocatalytic materials is mainly to add photocatalytic nanoparticles to polymer film-forming materials such as resins and cellulose, and finally coat and load them on the surface of the substrate to prepare a photocatalytic coating. However, the coating effect of polymer film-forming materials on photocatalytic nanoparticles will cause a decrease in photocatalytic activity. Directly using photocatalytic material precursor sol or nanoparticle film formation often requires subsequent high-temperature heat treatment (generally above 350°C) to achieve crystallization of the precursor material or to firmly bind the nanoparticles to the surface of the substrate, which limits the use of some heat-sensitive polymer substrates. Third, the metal filter currently used will rust during long-term use, resulting in peeling of the surface photocatalytic coating and reduced service life. Therefore, it is urgent to develop an efficient photocatalytic material and its loading technology to meet the application needs of the photocatalytic purification module of the current garbage deodorization system.
[0004] The Chinese invention patent CN114289007A proposed by the applicant discloses a method for preparing a ternary purification material for garbage odor treatment, wherein a C@Bi2O3 composite material is prepared by loading nanocarbon dots onto the surface of Bi2O3 nanofibers, and then the in-situ growth of TiO2 nanocrystals on the surface of the C@Bi2O3 composite material is achieved by controlling the hydrolysis of a titanium-containing precursor, so that the narrow-bandgap Bi2O3 nanofibers can absorb visible light, thereby constructing an efficient TiO2@C@Bi2O3 ternary composite photocatalytic material, and the TiO2@C@Bi2O3 composite material is fixed on the coating surface by ultraviolet light curing coating, thereby preparing a photocatalytic coating on the filter surface. However, this technology still has the following limitations: first, the preparation process of the ternary composite photocatalytic material is relatively complicated; second, the ultraviolet light curing coating used has a single function, which only plays a role in bonding and fixing the photocatalytic material, and has insufficient anti-corrosion ability for the metal filter.
[0005] Therefore, the present invention proposes a new solution to solve the above problems. Summary of the invention
[0006] The technical problem to be solved by the present invention is to overcome the deficiencies of the prior art and provide a method for preparing a photocatalytic deodorizing filter.
[0007] To solve the above technical problems, the solution of the present invention is:
[0008] A method for preparing a photocatalytic deodorizing filter is provided, which comprises the following steps:
[0009] (1) dissolving 1 to 5 parts by weight of polyvinyl pyrrolidone in 5 to 10 parts by weight of an organic solvent, and adding 3 to 8 parts by weight of a tungstate precursor to the resulting solution under magnetic stirring; continuing to stir for 1 hour and then standing at room temperature for 12 hours to obtain a homogeneous spinning solution; using an electrospinning device to form fibers from the spinning solution, and calcining the fibers at 500° C. for 1 to 5 hours to obtain porous WO3 nanofibers;
[0010] (2) treating the porous WO3 nanofibers in a plasma cleaning machine for 10 to 60 minutes, dispersing 1 part by mass of the nanofibers in 50 parts by mass of an acidic aqueous alcohol solvent to obtain a dispersion; dropping 1 part by mass of a 10% to 50% by mass titanium precursor alcohol solution into the dispersion, and then refluxing the reaction in an 80° C. water bath for 6 to 24 hours; filtering and washing the product, and then dispersing it in anhydrous ethanol at a mass fraction of 50% to obtain a TiO2@WO3 nanocomposite fiber ethanol dispersion;
[0011] (3) Take 1 part by mass of poly (3,4-ethylenedioxythiophene) / polystyrene sulfonic acid, 30-50 parts by mass of epoxy resin, 8-12 parts by mass of silica sol, 0.5-1.5 parts by mass of dicyandiamide, and 40-60 parts by mass of composite polar solvent, mix and continuously stir for 2-5 hours; apply to the surface of the metal filter by spraying process and leave for 10 minutes; continue to spray TiO2@WO3 nanocomposite fiber ethanol dispersion, and keep it at 170°C for 30 minutes to obtain a photocatalytic deodorization filter.
[0012] As a preferred embodiment of the present invention, the organic solvent in step (1) is at least one of propylene glycol methyl ether, dimethyl sulfoxide, and dimethylformamide; and the tungstate precursor is at least one of sodium metatungstate, ammonium metatungstate, and sodium tungstate.
[0013] As a preferred embodiment of the present invention, the electrospinning device in step (1) is composed of a high voltage generator, an injection pump and a fiber receiver; during electrospinning, the voltage is controlled to be 10 to 30 kV, the extrusion rate is 0.1 to 2 ml / h, and the receiving distance is 10 to 30 cm.
[0014] As a preferred embodiment of the present invention, the heating rate before the heat preservation calcination in step (1) is 1°C / min.
[0015] As a preferred embodiment of the present invention, the acidic hydroalcoholic solvent in step (2) is a mixed solvent formed by water and at least one of ethanol and isopropanol, and the pH value is adjusted to between 2 and 5 with nitric acid, and the mass of water accounts for 10 to 20% of the total mass of the mixed solvent.
[0016] As a preferred embodiment of the present invention, the operating power of the plasma cleaning machine in step (2) is 30W.
[0017] As a preferred embodiment of the present invention, in the titanium-containing precursor alcohol solution in step (2), the titanium-containing precursor is at least one of butyl titanate, titanium isopropoxide, and titanium tetrachloride, and the alcohol solvent is at least one of ethanol and isopropanol; the droplet acceleration rate of the titanium-containing precursor alcohol solution is 1 ml / min.
[0018] As a preferred embodiment of the present invention, the composite polar solvent in step (3) is at least two of propylene glycol methyl ether, dimethylformamide and isopropanol; and the solid content of the silica sol is 5-15%.
[0019] As a preferred embodiment of the present invention, the metal filter screen described in step (3) is any one of a stainless steel filter screen, an aluminum alloy filter screen, and a copper filter screen.
[0020] The present invention further provides a method for using the aforementioned slow-release deodorizing material, which is to install the sprayed metal filter in a photocatalytic purification module of a garbage deodorizing system to ensure that the metal filter can be irradiated by the light source configured by the photocatalytic purification module, and then use a duct exhaust fan to suck in the air inside the building to allow the malodorous gas containing ammonia and hydrogen sulfide to pass through the metal filter.
[0021] The implementation principle of the present invention:
[0022] 1. The present invention takes ammonia, hydrogen sulfide and other malodorous gases generated by domestic garbage in garbage transfer stations as the main purification and treatment objects, and aims at the problems of separation of photogenerated carriers and improvement of photoquantum efficiency of photocatalytic materials. The following are proposed: (1) TiO2 quantum dots are loaded onto porous WO3 nanofibers to construct TiO2@WO3 nanoheterojunctions, and the conduction of electrons by poly(3,4-ethylenedioxythiophene) / polystyrene sulfonic acid in the coating is utilized to promote the efficient separation of photogenerated carriers and improve photoquantum efficiency; (2) The porous structure is utilized to increase the specific surface area and further enhance the photocatalytic activity of the composite material.
[0023] 2. To address the problem of photocatalytic nanoparticle loading, the present invention adopts a two-step method to prepare the photocatalytic coating. First, a layer of epoxy resin-based wet film is sprayed on the filter substrate, and then TiO2@WO3 nanocomposite fibers are sprayed on the surface of the epoxy resin-based wet film. Finally, the epoxy resin-based wet film is cured by heating to fix the TiO2@WO3 nanocomposite fibers on the coating surface, thereby obtaining a photocatalytic coating on the filter surface.
[0024] 3. In order to solve the rust problem of metal filter during long-term use, the TiO2@WO3 nanocomposite fiber of the present invention uses epoxy resin with anti-corrosion ability as a film-forming material, and improves the coating's ability to conduct electrons by adding poly(3,4-ethylenedioxythiophene) / polystyrene sulfonic acid to avoid corrosion caused by static electricity accumulation and potential difference; the epoxy resin film layer is enriched by silica sol to improve the coating's ability to resist the penetration of corrosive media, thereby further improving the coating's anti-corrosion performance.
[0025] 3. Compared with the technical solution of patent CN114289007A, the preparation process of the TiO2@WO3 binary photocatalytic material proposed in the present invention is more convenient; the coating used not only realizes the bonding and fixation of the photocatalytic material, but also improves the corrosion resistance of the metal filter, and is also beneficial to the transfer of interface charges and improves the quantum efficiency of the photocatalytic material.
[0026] Compared with the prior art, the present invention has the following beneficial effects:
[0027] 1. The present invention constructs an efficient TiO2@WO3 nanofiber composite photocatalytic system. Compared with commercial nitrogen-doped TiO2 photocatalytic materials, the photocatalytic material of the present invention has higher visible light catalytic activity.
[0028] 2. The two-step photocatalytic coating preparation process proposed in the present invention solves the problem of photocatalytic performance degradation caused by the coating effect of polymer film-forming materials on photocatalytic nanoparticles in traditional methods. In addition, the photocatalytic material is mainly located on the surface of the coating where the photocatalytic reaction occurs, and there is no photocatalytic material inside the coating, thereby avoiding the waste of photocatalytic material.
[0029] 3. The present invention adopts a conductive epoxy resin coating to fix the TiO2@WO3 nanocomposite fiber on the filter surface, promote the separation of photogenerated carriers of TiO2@WO3, and improve the corrosion resistance of the metal filter. DETAILED DESCRIPTION
[0030] The present invention is further described in detail below in conjunction with specific embodiments:
[0031] The method for preparing the photocatalytic deodorizing filter of the present invention comprises the following steps:
[0032] (1) dissolving 1 to 5 parts by weight of polyvinyl pyrrolidone in 5 to 10 parts by weight of an organic solvent, and adding 3 to 8 parts by weight of a tungstate precursor to the resulting solution under magnetic stirring; continuing to stir for 1 hour and then standing at room temperature for 12 hours to obtain a homogeneous spinning solution; using an electrospinning device to form the spinning solution into fibers, heating the fibers to 500° C. at a rate of 1° C. / min, and calcining them at this temperature for 1 to 5 hours to obtain porous WO3 nanofibers;
[0033] The organic solvent is at least one of propylene glycol methyl ether, dimethyl sulfoxide and dimethylformamide; the tungstate precursor is at least one of sodium metatungstate, ammonium metatungstate and sodium tungstate. The electrospinning device is composed of a high voltage generator, an injection pump and a fiber receiver; during electrospinning, the voltage is controlled to be 10 to 30 kV, the extrusion rate is 0.1 to 2 ml / h, and the receiving distance is 10 to 30 cm.
[0034] (2) treating the porous WO3 nanofibers in a plasma cleaning machine for 10 to 60 minutes, dispersing 1 part by mass of the nanofibers in 50 parts by mass of an acidic aqueous alcohol solvent to obtain a dispersion; dropping 1 part by mass of a 10% to 50% by mass titanium precursor alcohol solution into the dispersion, and then refluxing the reaction in an 80° C. water bath for 6 to 24 hours; filtering and washing the product, and then dispersing it in anhydrous ethanol at a mass fraction of 50% to obtain a TiO2@WO3 nanocomposite fiber ethanol dispersion;
[0035] The acidic water-alcohol solvent is a mixed solvent formed by water and at least one of ethanol and isopropanol, and the pH value is adjusted to between 2 and 5 with nitric acid, and the mass of water accounts for 10 to 20% of the total mass of the mixed solvent. The operating power of the plasma cleaning machine is 30W. The drop rate of the titanium-containing precursor alcohol solution is 1ml / min. In the titanium-containing precursor alcohol solution, the titanium-containing precursor is at least one of butyl titanate, titanium isopropoxide, and titanium tetrachloride, and the alcohol solvent is at least one of ethanol and isopropanol.
[0036] (3) Take 1 part by mass of poly (3,4-ethylenedioxythiophene) / polystyrene sulfonic acid, 30-50 parts by mass of epoxy resin, 8-12 parts by mass of silica sol, 0.5-1.5 parts by mass of dicyandiamide, and 40-60 parts by mass of composite polar solvent, mix and continuously stir for 2-5 hours; apply to the surface of the metal filter by spraying process and leave for 10 minutes; continue to spray TiO2@WO3 nanocomposite fiber ethanol dispersion, and keep it at 170°C for 30 minutes to obtain a photocatalytic deodorization filter.
[0037] The composite polar solvent is at least two of propylene glycol methyl ether, dimethylformamide and isopropyl alcohol; the solid content of the silica sol is 5-15%. The metal filter is any one of a stainless steel filter, an aluminum alloy filter and a copper filter.
[0038] In actual use, the sprayed metal filter is installed in the photocatalytic purification module of the garbage deodorization system to ensure that the metal filter can be illuminated by the light source configured by the photocatalytic purification module, and then the internal air of buildings in places such as garbage transfer stations is sucked in by a duct exhaust fan to allow the odorous gas containing ammonia and hydrogen sulfide to pass through the metal filter.
[0039] The garbage deodorization system and the photocatalytic purification module can both adopt existing technologies. The main structure of the garbage deodorization system at least includes a ventilation duct, an exhaust fan, and a photocatalytic purification module. The photocatalytic purification module is a commercially available product, or is manufactured by referring to public literature. For example, Chinese patent CN218221851U records a ternary purification module for gas deodorization, in which a plurality of groups of horizontally arranged fluorescent lamps are arranged in its main box, and a ternary purification net is arranged between adjacent lamp groups; the angle between the blade and the horizontal plane is adjusted by using the air guide plate structure to achieve control of the air flow path, thereby improving the air purification treatment effect or efficiency of the equipment.
[0040] The following examples can help professionals in this field to more fully understand the present invention, but they do not limit the present invention in any way. Photocatalytic deodorizing filters were successfully prepared through 8 examples, and the test data in each example is shown in Table 1 below.
[0041] Table 1 Example data table
[0042]
[0043]
[0044] Photocatalytic deodorization filter photocatalytic purification performance test method: (1) Test materials and equipment
[0045] A photocatalytic deodorizing filter measuring 45cm×45cm; a glove box measuring 60cm×60cm×80cm, with a downward-blowing fan and two 24W LED white light sources on the top of the glove box; a gas injector; and a Japan Riken GX-6000 gas detector.
[0046] (2) Test steps
[0047] ①Install the photocatalytic deodorization filter into the glove box and place it against the inner wall of the glove box at an angle of 60 degrees to the bottom of the glove box to seal the glove box. Use the injector to inject a certain amount of test gas into the glove box so that the initial concentration of the target gas in the glove box is maintained at a certain value a0 (ammonia about 200ppm, hydrogen sulfide about 50ppm).
[0048] ② Turn on the light source and fan, and after 2 hours of photocatalytic reaction, test the target gas concentration a in the glove box. t ; The target gas removal rate P can be calculated by the following formula to characterize the photocatalytic purification performance of the photocatalytic deodorization filter.
[0049]
[0050] 1. Comparison with existing photocatalytic materials:
[0051] Under the same test conditions, the ammonia removal rate of the existing commercial nitrogen-doped TiO2 photocatalytic material is 74.7%, and the hydrogen sulfide removal rate is 68.5%. The visible light catalytic performance of the photocatalytic deodorization filter prepared in each embodiment of the present invention is better than that of the commercial nitrogen-doped TiO2 photocatalytic material (data are shown at the end of Table 1).
[0052] 2. Comparison with patent technology CN114289007A:
[0053] Compared with the product in the patent document, the product of the present invention has the same ammonia and hydrogen sulfide removal rate performance, but the photocatalytic material preparation process is more convenient. In addition, according to the method in the patent document, a ternary purification material for garbage odor treatment is prepared using an aluminum alloy filter screen, and the filter screen size is consistent with the above test. Then a neutral salt spray test is carried out according to the standard GB / T 10125-2012. The results show that after 480 hours of the salt spray test, the sample prepared by the method described in the patent document CN114289007A rusts, while the sample of the present invention is still intact.
[0054] Finally, it should be noted that the above examples are only specific implementation examples of the present invention. Obviously, the present invention is not limited to the above implementation examples, and there are many variations. All variations that can be directly derived or associated with the content disclosed by a person skilled in the art should be considered as the protection scope of the present invention.
Claims
1. A method for preparing a photocatalytic deodorizing filter, characterized in that: The following steps are involved: (1) dissolving 1 to 5 parts by weight of polyvinyl pyrrolidone in 5 to 10 parts by weight of an organic solvent, and adding 3 to 8 parts by weight of a tungstate precursor to the resulting solution under magnetic stirring; continuing to stir for 1 hour and then standing at room temperature for 12 hours to obtain a homogeneous spinning solution; using an electrospinning device to form fibers from the spinning solution, and calcining the fibers at 500° C. for 1 to 5 hours to obtain porous WO3 nanofibers; (2) treating the porous WO3 nanofibers in a plasma cleaning machine for 10 to 60 minutes, dispersing 1 part by mass of the nanofibers in 50 parts by mass of an acidic aqueous alcohol solvent to obtain a dispersion; dropping 1 part by mass of a 10% to 50% by mass titanium precursor alcohol solution into the dispersion, and then refluxing the reaction in an 80° C. water bath for 6 to 24 hours; filtering and washing the product, and then dispersing it in anhydrous ethanol at a mass fraction of 50% to obtain a TiO2@WO3 nanocomposite fiber ethanol dispersion; (3) Take 1 part by mass of poly (3,4-ethylenedioxythiophene) / polystyrene sulfonic acid, 30-50 parts by mass of epoxy resin, 8-12 parts by mass of silica sol, 0.5-1.5 parts by mass of dicyandiamide, and 40-60 parts by mass of composite polar solvent, mix and continuously stir for 2-5 hours; apply to the surface of the metal filter by spraying process and leave for 10 minutes; continue to spray TiO2@WO3 nanocomposite fiber ethanol dispersion, and keep it at 170°C for 30 minutes to obtain a photocatalytic deodorization filter.
2. The method according to claim 1, characterized in that The organic solvent described in step (1) is at least one of propylene glycol methyl ether, dimethyl sulfoxide, and dimethylformamide; the tungstate precursor is at least one of sodium metatungstate, ammonium metatungstate, and sodium tungstate.
3. The method according to claim 1, characterized in that: The electrospinning device in step (1) is composed of a high voltage generator, an injection pump and a fiber receiver; during electrospinning, the voltage is controlled to be 10 to 30 kV, the extrusion rate is 0.1 to 2 ml / h, and the receiving distance is 10 to 30 cm.
4. The method according to claim 1, characterized in that The heating rate before the heat preservation calcination in step (1) is 1°C / min.
5. The method according to claim 1, characterized in that The acidic hydroalcoholic solvent in step (2) is a mixed solvent formed by water and at least one of ethanol and isopropanol, and the pH value is adjusted to between 2 and 5 with nitric acid, and the mass of water accounts for 10 to 20% of the total mass of the mixed solvent.
6. The method according to claim 1, characterized in that The operating power of the plasma cleaning machine described in step (2) is 30W.
7. The method according to claim 1, characterized in that In the titanium-containing precursor alcohol solution in step (2), the titanium-containing precursor is at least one of butyl titanate, titanium isopropoxide, and titanium tetrachloride, and the alcohol solvent is at least one of ethanol and isopropanol; the droplet acceleration rate of the titanium-containing precursor alcohol solution is 1 ml / min.
8. The method according to claim 1, characterized in that: The composite polar solvent in step (3) is at least two of propylene glycol methyl ether, dimethylformamide and isopropanol; and the solid content of the silica sol is 5-15%.
9. The method according to claim 1, characterized in that: The metal filter described in step (3) is any one of a stainless steel filter, an aluminum alloy filter, and a copper filter.
10. A method for using the photocatalytic deodorizing filter prepared by the method described in any one of claims 1 to 9, characterized in that: The sprayed metal filter is installed in the photocatalytic purification module of the garbage deodorization system to ensure that the metal filter can be illuminated by the light source configured by the photocatalytic purification module, and then the air inside the building is sucked in by a duct exhaust fan to allow the odorous gas containing ammonia and hydrogen sulfide to pass through the metal filter.
Citation Information
Patent Citations
Preparation method of ternary purification material for garbage odor treatment
CN114289007A
Ternary purification module for gas deodorization
CN218221851U